2018
DOI: 10.1111/aas.13215
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged vasopressor support during hip‐fracture surgery is a risk factor for enhanced mortality

Abstract: Vasopressor treatment is common during hip fracture surgery. Patients treated with VP infusion ≥3 hours have increased mortality, while patients treated with injections or infusion <3 hours have not. We suggest that the prolonged use of VP treatment is linked to increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This study identified the risk factors for tibial plateau fractures combined with intercondylar eminence fractures, which included patients who were aged over 74 years and retired. The findings are consistent with other investigations. Lee et al .…”
Section: Discussionsupporting
confidence: 94%
“…This study identified the risk factors for tibial plateau fractures combined with intercondylar eminence fractures, which included patients who were aged over 74 years and retired. The findings are consistent with other investigations. Lee et al .…”
Section: Discussionsupporting
confidence: 94%
“…NHFS does not discriminate between comorbidities, omitting subjective grading among them. Low haemoglobin (<100 g/L = 1 p), is an objective value capturing both fracture blood loss as well as preoperative anaemia, factors affecting the peri‐operative care including blood transfusions and intraoperative hemodynamic stability, i.e., the need of vasopressors 16 . Finally, dementia, (captured by SPMSQ = 1 p), and dependent living (1 p) are factors connected to frailty, 17 but more easily assessed by NHFS.…”
Section: Discussionmentioning
confidence: 99%